FOREIGN LANGUAGE LEARNING: DIFFICULTIES AND IMPROVEMENT OF THE STUDY PROCESS - Žegunienė, Vaida; Parišauskienė, Dalia (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2017)
The idea about knowing well any foreign language is very inspirational. People who know two or more foreign languages are admired and give people a hope to learn a new language easily. Consequently, this nice idea ends with the difficulties that students face while learning a new language. Only the infinitive desire could help student to learn something new. Attempts are really important thing in learning language, but difficulties can stop and isolate from the learning process. Scientists constantly have been estimating various kinds of learning difficulties and people who are undergoing difficulties of their studies. Frequently students face with academic failures, but according to the scholars, there is a way to avoid them – making learning more modernized by incorporating various innovative technologies as a motivational tool.Teacher’s role, without any concerns, has a great influence on a person’s life. Intellectual development starting with the primary classes to the university auditoriums and even future career largely depends on a teacher, who is responsible for providing valuable information and deciding on the methods as well as motivational tools to be applied.The research and data acquired revealed the students’ attitude towards learning of foreign language. It was noted that it is a very complicated and laborious procedure requiring long time and sustained efforts. During the process of foreign language acquisition, as the research results demonstrate, students confront with variety of difficulties. The respondents noted that the most topical difficulties are as follows: poor knowledge from secondary school, lack of practice, inefficient time management, etc. Therefore, in order to achieve prodigious results, the process of efficient language acquisition has to incorporate new educational trends, innovative study methods and practices, and appropriate motivational tools. Students participating in the survey specified that they would be satisfied by participating in modern innovative teaching and learning activities and having more contact hours for their lectures, and although the role of motivation cannot be denied.